IMPLEMENTATION OF SANCTIONS FOR VIOLATIONS OF THE POLICE PROFESSIONAL CODE OF ETHICS IN ACCORDANCE WITH THE REPUBLIC OF INDONESIA POLICE LAW NUMBER 7 OF 2022 AT THE SURABAYA POLICE HEADQUARTERS - Sukanto; Soekorini, Noniek; Astutik, Sri (Case Law : Journal of Law, 2025)
The police code of ethics is a moral guideline and aims to prevent abuse of authority and increase accountability. Its implementation is often hampered by the lack of knowledge of police officers. Every Polri personnel is expected to demonstrate integrity and ethics in their duties. The type of research that the author uses in this study is sociological/empirical research, namely legal research with primary data or data obtained directly from the source. The results of the study indicate that cases of violations of the police profession code of ethics at the Surabaya City Resort are known to have violations committed, namely violations of personality ethics, community ethics, institutional ethics, where in the application of sanctions are carried out with ethical sanctions, and administrative sanctions including dishonorable dismissal from the police institution. This study also discusses the factors that influence the enforcement of the code of ethics of police members in improving the professionalism of the Police consisting of two factors, namely external factors, namely strengths and constraints, while internal factors are related to strengths, weaknesses and culture.